Językowy sposób wyrażania doświadczenia mistycznego w polskim tłumaczeniu Nocy ciemnej św. Jana od Krzyża - Gawrońska-Garstka, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The article presents the issues of mystical language in the book The Dark Night St. John of the Cross. The analysis of the material shows rich repertoire of linguistic forms used by the author. The characteristics of mystical language: expression, simple syntax, dialogue, subjectivity, persuasion, symbolism and ambiguity.